Assessing urban design factors for walkable areas: evidence from Dubai - Arar, Mohammad; Kazaz, Kareen (Frontiers in Built Environment, 2025)
Walkability ratings in the GCC are generally low. Beyond climate conditions, modern lifestyle shifts such as increased reliance on automobiles, home deliveries, remote work, and digital connectivity have contributed to the decline of walking as a primary mode of transport. While previous research has identified urban design factors that influence walkability, there is limited empirical evidence on how these factors operate within Dubai’s unique urban context. This paper investigates the impact of urban design on perceived walkability using objective site analysis. Based on a review of the existing literature, Ewing and Handy’s model was selected for its strong explanatory power; accounting for 95% of walkability variation across five key urban design factors: Imageability, Enclosure, Human Scale, Transparency, and Complexity. The model also identifies Human Scale as the most significant factor influencing walkability, which informed the study’s hypothesis that Human Scale would emerge as the primary predictor in the selected sites. Notably, Complexity consistently emerged as a strong predictor, underscoring the importance of spatial diversity and visual richness in enhancing pedestrian experiences. An objective built environment analysis was also conducted using Ewing and Handy’s field guide to assess the five walkability factors across the selected sites. This analysis highlighted which sub-factors, such as landscape features, positively contributed to walkability. However, it also revealed the assessments, particularly in how each site ranked across the design factors. The findings affirm the relevance of Ewing and Handy’s model in assessing overall walkability; however, they also suggest that additional variables may be needed to fully capture the dynamics of walkability in Dubai’s urban context. While the model identifies Human Scale as the most significant factor, an insight that shaped this study’s original hypothesis, the results reveal that this may not hold true uniformly across all locations. Instead, Complexity consistently emerged as a stronger predictor, emphasizing the role of spatial diversity and visual richness in shaping the pedestrian experience. These insights offer valuable guidance for urban planners and policymakers aiming to enhance walkability, particularly in the design and development of low-rise areas intended to attract pedestrians.